REFRAMING URBAN GOVERNANCE THROUGH PARTICIPATION: AN ETHNOGRAPHIC INQUIRY INTO PUBLIC HOUSING MANAGEMENT IN PALEMBANG, INDONESIA - Doris Febriyanti; Bambang Wicaksono; Halimah Abdul Manaf (Universitas Negeri Yogyakarta, 2025)
This study examines participatory urban governance in the management of public rental apartments (Rusunawa) in the 24-26 Ilir area of Palembang City, Indonesia. It explores how fragmented institutional arragements and weak coordination among government agencies shape the daily governance of public housing and how residents respond. Using a qualitative ethnographic approach, data were gathered through participant observation, in depth interviews with 20 informants, and field documentation. The findings show that governance of public housing in Palembang operates within institutional fragmentation, where the absence of clear authority and coordination creates governance vacuums that are filled by local actors( neighborhood heads and senior residents). Citizen participation emerges as an adaptive, community-drivenpractice that sustains everyday management despite limited formal support. This participation is largely informal, negotiated, and rooted in social solidarity rather than formal policy mechanisms. The study reframes urban governance as a lived and negotiated process, emphasizing that sustainable public housing management requires recognizing local capacities, institutionalizing deliberative space, and collaborative support from municipal authorities. The research contributes to the discourse on particatory governance in mid-sized cities of the Global South by highlighting the value of community-based management as a foundation for inclusive and context-responsive urban policy.